PENERAPAN DENDA MURABAHAH MENURUT FATWA DEWAN SYARIAH NASIONAL DSN/MUI (STUDI DI PT. BANK MUAMALAT INDONESIA CABANG PADANGSIDIMPUAN) - Fadli Fadli (JURIS (Jurnal Ilmiah Syariah), 2017)
The law of sharia banks as a monetary intermediary institution which is the main contributor and main funding activity is that various products and mechanisms are facing various dynamics, such as the fact that some customers cannot fulfill their obligations within the prescribed time, resulting in delayed payment delays. In this case, the bank tried to overcome the problem tersbut by applying a penalty on financing in which accommodate the opinion of the Council of Advocates of Islamic Law of the National MUI where the customer can be fined if the customer is late in making deferred payments. In Islam a person is obliged to respect and obey each trust or agreement entrusted to him. If he has obtained a bank loan or financing, then he already trusts other people (depositors or owners of capital) so that if he did default, then it can be said he has done default and can be subjected to sanctions or actions according to the conditions and reasons. In this case because customers do default bank will suffer losses, because it causes bank spend more extra expenses ranging from administrative affairs, to hire a lawyer. The National Islamic Law Council of MUI in its fatwa Number 17/ DSN-MUI / IX / 2000 on Sanctions against Clients Delaying Payments enables the banks of sharia to assume  customer to be able to but does not fulfill the obligations of syari 'ah.